THE ANALYSIS OF SALES PROMOTION, PERSONAL SELLING AND ADVERTISING ON CONSUMER PURCHASE DECISION AT HOTEL SEDONA MANADO - Kereh, Grace M. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
The tourism sector is one of the businesses that relies on the government to obtain foreign exchange. That is why this sector increasingly has an important role in the Indonesian economy, either as a source of foreign exchange earnings or as a business opportunities in the utilization of small and medium-sized industries. Nowadays, because the competition in the hospitality industry is very tight, therefore it need strategies to attract new consumers. Hotel Sedona Manado as one of the five star hotels is also doing various promotional mix strategies to attract consumer purchase. This research is to examine the influential factors on consumersâ€™ purchase decision at Hotel Sedona Manado.Â  Discriminant analysis is the statistical method used in the analysis of this research, with sales promotion, personal selling, advertising and consumer purchase decision as the variables. Theories supporting this research are sales promotion, personal selling, advertising, and consumer purchase decision. The population that is mainly observed in this research is people who have stayed at Hotel Sedona Manado with the sample size as many as 50 respondents. The result shows that both purchaser and non-purchaser of Hotel Sedona Manado have significant differences, which sales promotion is the most dominant variable in discriminating consumer purchase decision, followed by personal selling and advertising. Keywords: sales promotion, personal selling, advertising, consumer purchase decision